Teacher's Strategy to Create Fun Learning in Elementary School - Servista Bukit; Eny Dwi Marcela; Ernawati Ernawati (CV. Tripe Konsultan, 2023)
Fun learning has become a demand for learning from students. Students as learning subjects need pleasure as the essence of human life needs. Students who feel happy and are not pressured during learning will be able to follow the learning process well. Even with the fun that students have, it can help them to improve learning outcomes and can even form good character within them. The focus of this research is to describe various teacher strategies in realizing fun learning in elementary schools. This research is a descriptive research with a qualitative approach. The research method is the method of literature review. The results of this study describe several fun learning strategies such as constructivist learning methods, edutainment approaches, character-based edutainment learning, and joyful learning. The learning strategy is expected to be applied by elementary school teachers in learning. By implementing this learning strategy, it can realize learning that is in favor of students to realize the profile of Pancasila students in the era of independent learning.